Effectiveness of an improvement programme to prevent interruptions during medication administration in a paediatric hospital: a preintervention–postintervention study - Dall'Oglio, Immacolata (BMJ Open, 2017)
OBJECTIVE: To assess the effectiveness of an improvement programme to reduce the number of interruptions during the medication administration process in a paediatric hospital. DESIGN AND METHODS: A prestudy–post study design was used to monitor nursing interruptions during medication cycles in a paediatric hospital. Interruptions were reported on an observation sheet (MADOS-P) adapted to the paediatric context. SETTING: A 600-bed tertiary paediatric research hospital in Italy. INTERVENTION: The interventions included a yellow sash worn by nurses during medication cycles, a yellow-taped floor area indicating the ‘No interruption area’, visual notices in the medication areas, education sessions for healthcare providers and families, patient and parent information material. RESULTS: 225 medication cycles were observed before the intervention (T0) and 261 after the intervention (T1). The median of interruptions occurring in each cycle decreased significantly from baseline to postintervention (8.0 vs 2.0, p=0.002), as the rate ratios (interruptions/patient post–pre ratio: 0.34; interruptions/medication post–pre ratio: 0.37; interruptions/hour of medication cycle post–pre ratio: 0.53, p<0.001). During preintervention, the main causes of interruptions were ‘other patients’ (19.9%), ‘other nurses’ (17.2%) and ‘conversation’ (15.7%); during postintervention, they were ‘other nurses’ (26.1%), ‘conversation’ (18.2%) and ‘other patients’ (17.4%). CONCLUSIONS: This bundle of interventions proved to be an effective improvement programme to prevent interruptions during medication administration in a paediatric context.